2005
DOI: 10.1073/pnas.0502662102
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonality of familial murine adenomas: Analyses of mouse chimeras with low tumor multiplicity suggest short-range interactions

Abstract: In previous studies demonstrating the polyclonal structure of familial intestinal adenomas, high tumor multiplicity made it difficult to eliminate the possibility that polyclonality arose by the random collision of distinct initiated clones as opposed to some form of clonal interaction. We sought to test further the random collision hypothesis. Chimeric mice carrying the multiple intestinal neoplasia (Min) mutation of the adenomatous polyposis coli gene (Apc) and homozygous for the tumor resistance allele of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 21 publications
(17 reference statements)
3
66
1
Order By: Relevance
“…It has been suggested, based on the analysis of chimeric Apc Min/ϩ mice, that tumors in the small intestine arise by active interactions between crypts promoting loss of Apc and thus resulting in the formation of polyclonal adenomas (36). In that study, however, only 22% of all tumors were identified as polyclonal.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…It has been suggested, based on the analysis of chimeric Apc Min/ϩ mice, that tumors in the small intestine arise by active interactions between crypts promoting loss of Apc and thus resulting in the formation of polyclonal adenomas (36). In that study, however, only 22% of all tumors were identified as polyclonal.…”
Section: Discussioncontrasting
confidence: 40%
“…Since Cre-mediated recombination is irreversible and the majority of tumors in Apc Min/ϩ mice are considered to be monoclonal (22,27,36), this suggests that Dnmt3b deletion occurred after tumor initiation during tumor growth. Two observations are consistent with this idea.…”
Section: Dnmt3b Is Activated In the Intestinal Tumors Of Apcmentioning
confidence: 99%
“…This finding may reflect the increased level of normal epithelial and stromal admixture in the nonpedunculate mouse tumors that are dissected from the small intestine. Alternatively, this broad distribution of allelic ratios may reflect the known polyclonality of Min tumors (21) or differences between tumors of the small intestine and the colon. By contrast, the high concordance between the majority of gLOH vs. cLOH allelic ratios in F1-Pirc tumors and between the gMOH vs. cMOH allelic ratios in normal epithelium indicates that these pedunculate colonic rat tumors are dissected with less admixture of normal epithelial and stromal tissue, resulting in more highly defined LOH and MOH classes.…”
Section: Discussionmentioning
confidence: 99%
“…The F1-Pirc rat provides a large proportion of colon tumors that are highly enriched for epithelial tumor material. The residual level of admixture between LOH and MOH classes may be owing to the nonmedullary nature of all intestinal tumors, or it may reflect polyclonality as documented in the mouse and human (21,22,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation